2015
DOI: 10.1007/s40257-015-0149-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Gastrointestinal Symptoms in Long-Term Treated Dermatitis Herpetiformis Patients: A Cross-Sectional Study in Finland

Abstract: We conclude that long-term GFD-treated DH patients do not suffer from the burden of dietary treatment and have a quality of life comparable to that of controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
4
15
0
3
Order By: Relevance
“…In the present study, the coeliac disease controls were further found to have worse self-reported general health, and they had more gastrointestinal symptoms at the time of the study compared to the DH patients. These results fit with our recent study that likewise found a better quality of life and fewer gastrointestinal symptoms among long-term treated DH patients compared to treated coeliac disease patients [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the coeliac disease controls were further found to have worse self-reported general health, and they had more gastrointestinal symptoms at the time of the study compared to the DH patients. These results fit with our recent study that likewise found a better quality of life and fewer gastrointestinal symptoms among long-term treated DH patients compared to treated coeliac disease patients [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…We further detected an improvement in DH patients' life quality after one year of GFD treatment, reaching the level of healthy controls in most values measured, and being superior to that in the classical coeliac disease patients from the same series (6). We have previously shown in a different series that DH patients' quality of life is comparable to that of the healthy population even in the long term (18), which supports our present results. In this study female patients with DH were found to have a poorer quality of life than male patients with DH.…”
Section: Discussionsupporting
confidence: 90%
“…Female patients had a longer diagnostic delay in the current study compared with male patients, again as has been shown in coeliac disease (22). Furthermore, female DH and coeliac disease patients have been shown to have more severe GI symptoms than males (18,23). The above-mentioned factors are also both linked to diminished quality of life in coeliac disease (5,19,24), and thus might offer other explanations for the gender differences in quality of life.…”
Section: Discussionsupporting
confidence: 65%
“…However, according to current knowledge, the QoL of patients with DH seems to be reduced, but importantly, already after adherence to a GFD for 1 year, the QoL increases to the level of controls (35). The positive impact of GFD on DH patients' QoL is also supported by another study, in which the Qol of long-term GFD-treated DH patients was equal to that of controls, and slightly better than that of long-term treated coeliac patients (74).…”
Section: Long-term Prognosis On a Gluten-free Dietmentioning
confidence: 75%